Chirality matters: stereo-defined phosphorothioate linkages at the termini of small interfering RNAs improve pharmacology in vivo. Issue 3 (15th July 2021) - Jahns, Hartmut; Taneja, Nate; Willoughby, Jennifer L S; Akabane-Nakata, Masaaki; Brown, Christopher R; Nguyen, Tuyen; Bisbe, Anna; Matsuda, Shigeo; Hettinger, Matt; Manoharan, Rajar M; Rajeev, Kallanthottathil G; Maier, Martin A; et al.
Abstract: A critical challenge for the successful development of RNA interference-based therapeutics therapeutics has been the enhancement of their in vivo metabolic stability. In therapeutically relevant, fully chemically modified small interfering RNAs (siRNAs), modification of the two terminal phosphodiester linkages in each strand of the siRNA duplex with phosphorothioate (PS) is generally sufficient to protect against exonuclease degradation in vivo . Since PS linkages are chiral, we systematically studied the properties of siRNAs containing single chiral PS linkages at each strand terminus. We report an efficient and simple method to introduce chiral PS linkages and demonstrate that R p diastereomers at the 5′ end and S p diastereomers at the 3′ end of the antisense siRNA strand improved pharmacokinetic and pharmacodynamic properties in a mouse model. In silico modeling studies provide mechanistic insights into how the R p isomer at the 5′ end and S p isomer at the 3′ end of the antisense siRNA enhance Argonaute 2 (Ago2) loading and metabolic stability of siRNAs in a concerted manner.